Effect Of Audit Committee Financial Competence On Quality Of Financial Reporting Among Non-Commercial State Corporations In Kenya - Mwangi, Kirubi (Archives of Business Research, 2018)
The purpose of this research was to establish the effect of audit committee financial competence on quality of financial reporting in non-commercial state corporations in Kenya. The research was founded on agency theory, lending credibility theory and theory of inspired confidence. Empirical evidence on influence of audit committee financial competence on quality of financial reporting was reviewed analysed and research gaps identified. The research adopted descriptive research design and the target population was the seventy two non-commercial state corporations that existed subsequent to the introduction of The National Treasury guidelines in 2005 on formation and operationalization of audit committees in the public sector in Kenya. Descriptive statistics used in presentation of findings include frequencies, mean and standard deviation, while inferential statistics used are correlation and regression analysis. Regression analysis was employed to measure the relationship between dependent and independent variables. The findings from both correlation and regression analysis revealed that audit committee financial competence had a statistically significant relationship with the quality of financial reporting. The results revealed that audit committee financial competence reduced the ratio of queried transactions to annual budget of non-commercial state corporations in Kenya. From the findings, the research concluded that members of audit committees of non-commercial state corporations should have some level of financial competence in order to enhance the quality of their financial reporting and that audit committees should consist of members with knowledge in accounting and finance which provides a good basis for audit committee members to examine and analyse financial information.